PENGARUH KOMPETENSI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT TELKOM INDONESIA WITEL MEDAN - Situmorang, Astuti; Munthe, Kornel (Jurnal Manajemen dan Bisnis, 2015)
This study aimed to determine the effect of competence and discipline on employee performance provided by the Company PT Telkom Indonesia Witel Medan. PT Telkom Indonesia Witel Medan is the State Owned Enterprises engaged in the field of information and communication as well as service providers and telecommunications networks. Data collected through interviews and questionnaires. The total sample of 76 respondents were taken Proportionate Stratified Random Sampling. The results showed that the competence and discipline positive and significant effect partially on employee performance. Simultaneous test shows that the competence and discipline significant influence on employee performance. The coefficient of determination (R2) of 0.520 suggesting that variations in the performance of employees can be explained by changes in the competence and discipline of work by 52 percent, while 48 percent is explained by other variables not included in this study.